Providing an Integrative Approach in Humanitarian Training of Future Doctors in the Conditions of Interactive Learning - Larysa Maksymchuk (Pedagogical Discourse, 2014)
Research is devoted to the problem of the quality of modern medical specialist, which should be focused on professional communication, correct in terms of rules and style, situational, contextual and adequate. The requirements to the future doctors do not only have a high level of medical knowledge and special skills, but also the presence of multicultural competence, skills of working with colleagues, patients in typical situations related to medicine and health care. It leads teachers to use new learning technologies in order to provide successful interactive learning as the driving force to overcome the psychological barriers of professionally oriented communication.The article presents the advantages of integrated education, presented summary of actions of the teacher, it has been disclosed the essence of the integrative approach to professional humanitarian training of future doctors in terms of interactivity.